A Report of a Large Axillary Cystic Hygroma (a.k.a Lymphangioma) in a Newborn from a Tertiary Hospital in Northern Tanzania. (17th November 2020) - Lodhia, Jay; Philemon, Rune; Amsi, Patrick; Chilonga, Kondo; Msuya, David
Abstract : Introduction . Cystic hygroma is a rare condition of the lymphatic system that occurs mainly in children. They are found around the neck, axilla, inguinal, or thoracic regions. Case Presentation . A newborn female baby with a right-sided axillary mass since birth was admitted to our center. She was otherwise a healthy baby with noncontributory prenatal history. The mass was 12 cm in diameter and cystic. Wide excision of the mass was done, and histology confirmed cystic hygroma. Postoperatively, the baby did well clinically and was discharged. Conclusion . Due to its rare incidence, reports and literature on management of cystic hygroma are few. A multidisciplinary approach is vital to yield the best prognosis for this rare condition.